(untitled) (Fourth World Journal, 2026)
This paper explores the interaction between feminist and Indigenous epistemologies with a particular focus on Māori women in Aotearoa (New Zealand) and the contributions of Mana Wahine theory (the authority of Māori women). Māori are the Indigenous people of Aotearoa, with connections to land, environment, cultural traditions, and a worldview shaped by whakapapa (genealogy), wairua (spirituality), and collective identity. Colonization disrupted many of these traditions; however, Māori women have continued to hold and transmit Indigenous knowledge through the generations. This paper validates the healing practice of moko kauae (traditional female chin tattoo) as a prime example of Mana Wahine. The apaper examines how Western feminist approaches can both align with and diverge from Indigenous ways of knowing. Drawing on Mana Wahine theory and the lived experiences of Māori women, it affirms the centrality of cultural identity in understanding Māori women’s health and healing.